Young Agriculturists’ Journey: The Agricultural Science and Technology School Tracer Study - REGIDOR G. GABOY; TEODORA T. BATTAD; SOLEDAD S. MINA-ROGUEL; ROJELITO F. SISON (Universitas Jambi, Indonesia, 2019)
This study traced the graduates of Agricultural Science and Technology School (ASTS) in the Philippines using survey research. Majority of the 130 graduates were female and those who pursued college studies were taking-up agriculture-related courses. They oftentimes recognize the relevance of their learning from ASTS to their present undertakings. Hands-on experiences in doing projects had influence on the present occupational status of the graduates. Majority of the self-employed graduates are into agriculture-related endeavors. Work independence was considered the primary competency that they have gained from ASTS. They also strongly agreed on the competencies of the teacher as well as the facilities and equipment of the school. Agriculture is strongly important to the graduates and learning agricultural science in high school helped them get a good job. The field of agriculture was also found attractive for female students in the high school level. Students may also earn while studying. School administrators may adopt the curriculum being implemented by ASTS to maximize the opportunities of students to venture in the agriculture industry.